Research handbook on international procedural law - Gomula, Joanna; Wittich, Stephan; Stemeseder, Markus (Research handbooks in international law, 2024)
This comprehensive Research Handbook provides a detailed exploration of the principles and rules that impact the procedures and operation of international courts and tribunals. Within this framework, leading experts examine how the evolution of procedural rules and concepts has given rise to a distinct body of rules known as international procedural law. Diverse contributors from common and civil law backgrounds discuss the significance, sources and general principles of international procedural law and highlight crucial, yet often overlooked, international dispute resolution regimes. Specific problems related to the emergence of international procedural law, such as the interaction between international judicial regimes, are also unpacked and potential practical solutions investigated. The Research Handbook concludes by looking forwards, using a comparative analysis of the interactions between distinct international dispute resolution regimes to outline how mutual consideration and comity can lead to procedural congruence. The "Research Handbook on International Procedural Law" is an authoritative reference for students and scholars of arbitration and dispute resolution, constitutional and administrative law, and public international law. Discerning and practical, it will also act as a core resource for practitioners, government officials, judges, and members of adjudicative bodies